Determinants of Household Consumption Expenditure in Denpasar City - Athina Wulandari I Gusti Ayu; Ni Made Intan Priliandani (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Consumption expenditure is one of the indicators used to measure the objective welfare of society. The average per capita household consumption expenditure in Denpasar City has decreased since 2020-2022 but remains the highest compared to other districts in Bali Province. The purpose of this study was to analyze the economic and social aspects in influencing household consumption expenditure in Denpasar City. Based on the results of the analysis using multiple linear regression analysis techniques, it was found that age had a positive but insignificant effect, while income had a positive and significant effect on household consumption expenditure in Denpasar City. The implication of this study is that the income used to increase household consumption expenditure that is consistent is fixed income. For Balinese Hindu families, rahinan and menyama braya are mandatory consumption expenditures in addition to primary needs that must be met.